Performance of old and new maize hybrids at high plant densities in the tropical Guinea Savanna - Kamara, A.; Menkir, A.; Kureh, I.; Omoigui, L.; Ekeleme, F. (2006)
Genetic improvement of maize hybrids for superior stress tolerance has contributed to increased yield by allowing hybrids to be planted at higher plant populations. This study was conducted to evaluate the response of maize hybrids developed in the Nigerian Savanna from different eras to high plant densities. Field research was conducted in 2002 and 2003 at the experiment station of the Institute of Agricultural Research, Samaru in the northern Guinea savanna zone, Zaria, Nigeria. Six hybrids—two from 1980s, two from 1990s and two from the2000 eras—were evaluated at three plant densities using a split-plot design with three replications. Plant densities (53,333, 66,666, and 79,999 plants ha-1) constituted the main plots and the six hybrids were assigned to subplots. Plant densities above 53,333 plants ha-1reduced grain yield of hybrids, which might be due to the fact that the hybrids evaluated were selected at low plant densities and were therefore not tolerant to plant-density stress. It might also be due to the low yield potential in the experimental area, which did not allow yield increases at high plant densities. There were significant differences among the tested hybrids. The hybrids released in 2000 out-yielded the hybrids released in 1980 and 1990s at all plant densities. To improve maize grain yield at high plant densities, were commend that the hybrids be selected at high plant densities.